Uji aktivitas antibakteri fraksi n-heksan dan etil asetat daun kenanga (Cananga odorata (Lam.) Hook. F. & Thomson) terhadap bakteri Staphylococcus epidermidis - Sepriani, Ananda; Nasution , Haris Munandar; Mambang, D. Elysa Putri; Rahayu, Yayuk Putri (Journal of Pharmaceutical and Sciences, 2023)
Human life always coexists with various types of microbes. One of them is kenaga leaves (Cananga odorata (Lam.) Hook. F. & Thomson), which is a plant that can be used as a traditional medicine, one of which can be used to treat itching on human skin and can inhibit bacteria, one of which is Staphylococcus epidermidis. This research aimed to determine the types of secondary metabolite compounds contained in ylang-ylang leaves (Cananga odorata (Lam.) Hook. F. & Thomson) and to test the antibacterial activity of the n-hexane and ethyl acetate fractions of ylang-ylang leaves (Cananga odorata (Lam.) Hook. F. & Thomson). This research method includes simplicia characterization and phytochemical screening on simplicia powder and 96% ethanol extract. Extraction was done by maceration with 96% ethanol solvent, then liquid-liquid fractionation with n-hexane and ethyl acetate solvents. The antibacterial activity test was carried out by measuring the diameter of the inhibition zone using the agar diffusion method. The results of the examination of the characteristics of ylang-ylang leaf Simplicia powder (Cananga odorata (Lam.) Hook. F. & Thomson) showed that the water content was 7.33%, the water-soluble essence content was 26.48%, the total ash was 3.52%, and acid insoluble ash content 0.18%. The results of phytochemical screening showed alkaloids, flavonoids, saponins, glycosides, tannins, and steroids. The activity test results on the n-hexane, ethyl acetate, and ethanol extract fractions had antibacterial activity. The n-hexane fraction gave strong results against Staphylococcus epidermidis bacteria at a 70 mg/ml concentration with an inhibitory zone diameter of 12.37 mm. The ethyl acetate fraction was strong against Staphylococcus epidermidis bacteria at a 70 mg/ml concentration with an inhibition zone diameter of 12.98 mm.